Three blind mice and other stories - Christie, Agatha 1890-1976 (New York Berkley Books, 1984)
Contains nine short mystery stories by Agatha Christie, including the title work about a young couple who open a new guest house, not realizing one of their first customers is a murderer.
Three blind mice.--Strange jest.--Tape-measure murder.--The case of the perfect maid.--The case of the caretaker.--The third-floor flat.--The adventure of Johnnie Waverly.--Four and twenty blackbirds.--The love detectives.
"Formerly published as The mousetrap."
Keywords: Marple, Jane -- (Fictitious character) -- Fiction; Poirot, Hercule -- (Fictitious character) -- Fiction; Detective and mystery stories, English; Mystery fiction